2022
DOI: 10.3389/fonc.2022.892918
|View full text |Cite
|
Sign up to set email alerts
|

Unearthing novel fusions as therapeutic targets in solid tumors using targeted RNA sequencing

Abstract: Detection of oncogenic fusion genes in cancers, particularly in the diagnosis of uncertain tumors, is crucial for determining effective therapeutic strategies. Although novel fusion genes have been discovered through sequencing, verifying their oncogenic potential remain difficult. Therefore, we evaluated the utility of targeted RNA sequencing in 165 tumor samples by identifying known and unknown fusions. Additionally, by applying additional criteria, we discovered eight novel fusion genes that are expected to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Previously, such out-of-frame fusions have been shown to be stable, i.e., not rapidly degraded, but the specific function of the out-of-frame fragment remains unknown [192]. Fusions from this group are often assumed to be inactivating mutations [193], or are labeled passenger mutations or ignored altogether in analysis [135,194]. However, stable out-of-frame fusions with drastically distorted downstream amino acid sequences and passenger mutations possess the highest immunogenicity [190].…”
Section: Neoantigen Immunogenicitymentioning
confidence: 99%
“…Previously, such out-of-frame fusions have been shown to be stable, i.e., not rapidly degraded, but the specific function of the out-of-frame fragment remains unknown [192]. Fusions from this group are often assumed to be inactivating mutations [193], or are labeled passenger mutations or ignored altogether in analysis [135,194]. However, stable out-of-frame fusions with drastically distorted downstream amino acid sequences and passenger mutations possess the highest immunogenicity [190].…”
Section: Neoantigen Immunogenicitymentioning
confidence: 99%
“…For instance, intergenic‐breakpoint ROS1 rearrangements theoretically should not be transcribed due to the lack of a promoter, but studies have showed some of them can unequivocally produce functional fusion transcripts [ 17 ]. Besides that, the functional implications of rare fusions identified at the genomic level are not easily predictable [ 18 , 19 ]. Therefore, validation of genomic fusions at transcriptional level was critical to optimize treatment strategy.…”
Section: Introductionmentioning
confidence: 99%